Consumer perspective on influencers, the rising trend of digital marketing perspective: A qualitative research on generation Y - Akto, Gülşah (IGI Global, 2024)
Advances in digital media have affected consumer preferences and tendencies as they have impacted the field of marketing. Whilst digital marketing becomes more effective every day, influencer marketing has taken its place among the most popular marketing strategies of recent times. Defined as a personality that alters and influences the way other people behave, influencers have tried to shape consumers' preferences and purchasing behaviors by obtaining and evaluating information in different ways and promoting products and services. Although influencers have an impact on their followers' preferences, consumer opinions towards influencers are equally significant. This study aims to analyze consumers' views on the concept of influencers, why they follow influencers, and their perspectives on influencers' earnings and status. In addition, the study focused on how influencers' product and service promotions affect consumers' opinions about brands and companies and their purchasing behaviors. © 2024, IGI Global. All rights reserved.